Morbidity and mortality following acoustic neuroma excision in the United States: analysis of racial disparities during a decade in the radiosurgery era - McClelland, Shearwood (Oxford University Press, 2011)
Acoustic neuromas present a challenging problem, with the major treatment modalities involving operative excision, stereotactic radiosurgery, observation, and fractionated stereotactic radiotherapy. The morbidity/mortality following excision may differ by patient race. To address this concern, the morbidity of acoustic neuroma excision was assessed on a nationwide level. The Nationwide Inpatient Sample from 1994–2003 was used for analysis. Only patients admitted for acoustic neuroma excision were included (International Classification of Diseases, 9th edition, Clinical Modification = 225.1; primary procedure code = 04.01). Analysis was adjusted for several variables, including patient age, race, sex, primary payer for care, income in ZIP code of residence, surgeon caseload, and hospital caseload. Multivariate analyses revealed that postoperative mortality following acoustic neuroma excision was 0.5%, with adverse discharge disposition of 6.1%. The odds ratio for mortality in African Americans compared with Caucasians was 8.82 (95% confidence interval = 1.85–41.9, P = .006). Patients with high-caseload surgeons (more than 2 excisions/year), private insurance, and younger age had decreased mortality, better discharge disposition, and lower overall morbidity (P < .04). Neither hospital caseload nor median income were predictive factors. African Americans were 9 times more likely to die following surgery than Caucasians over a decade-long analysis. Given the relatively benign natural history of acoustic neuroma and the alarmingly increased mortality rate following surgical excision among older patients, African Americans, and patients receiving care from low-caseload surgeons, acoustic neuromas in these patient populations may be best managed by a more minimally invasive modality such as observation, fractionated stereotactic radiotherapy, or stereotactic radiosurgery.